The Role of Cytokines in the Functional Activity of Phagocytes in Blood and Colostrum of Diabetic Mothers - Gomes Fagundes, Danny Laura [UNESP]; Franca, Eduardo Luzia; Morceli, Glilciane [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Honorio-Franca, Adenilda Cristina (Hindawi Publishing Corporation, 2013)
Immune response changes induced by diabetes are a risk factor for infections during pregnancy and may modify the development of the newborn's immune system. The present study analyzed colostrum and maternal and cord blood of diabetic women to determine (1) the levels of the cytokines IFN-gamma and TGF-beta and (2) phagocytic activity after incubation with cytokines. Methods. Colostrum and maternal and cord blood samples were classified into normoglycemic (N = 20) and diabetic (N = 19) groups. Cytokine levels, superoxide release, rate of phagocytosis, bactericidal activity, and intracellular Ca2+ release by phagocytes were analyzed in the samples. Irrespective of glycemic status, IFN-gamma and TGF-beta levels were not changed in colostrum and maternal and cord blood. In maternal blood and colostrum, superoxide release by cytokine-stimulated phagocytes was similar between the groups. Compared to spontaneous release, superoxide release was stimulated by IFN-gamma and TGF-beta in normoglycemic and diabetic groups. In the diabetic group, cord blood phagocytes incubated with IFN-gamma exhibited higher phagocytic activity in response to EPEC, and maternal blood exhibited lower microbicidal activity. These data suggest that diabetes interferes in maternal immunological parameters and that IFN-gamma and TGF-beta modulate the functional activity of phagocytes in the colostrum, maternal blood, and cord blood of pregnant diabetic women.